VD_FINDINFO Décision / 2015 / 891 vom 2. Dezember 2015 - VD Tribunal cantonal (2015)
LIBÉRATION CONDITIONNELLE, REJET DE LA DEMANDE, PRONOSTIC, SÉJOUR ILLÉGAL | 86 al. 1 CP, 26 al. 1 let. a LEP, 38 al. 1 LEP, 393 CPP (CH)